2012
DOI: 10.3390/medicina48030020
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Femoral Neck Fractures: A Two-Year Follow-up

Abstract: Background and Objective. To identify the survival and standardized mortality ratio with respect to gender, age, and treatment method of patients treated for femoral neck fractures. Material and Methods. A retrospective review of medical records of 736 patients treated for femoral neck fractures at Vilnius University Emergency Hospital during 2004–2006 was carried out. Results. The overall 1- and 2-year survival rates were 77.4% and 67.1%, respectively. Lower survival rates were observed in the internal fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The incidence of femoral neck fracture is increasing at an exponential rate as a result of the longevity of the general population [ 2 ]. It is one of the most common consequences of injuries in the elderly population [ 3 ]. Despite advances in surgical techniques and medical care, the risk of nonunion and avascular necrosis (AVN) of femoral head after fixation have not changed appreciably in the last 50 years [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of femoral neck fracture is increasing at an exponential rate as a result of the longevity of the general population [ 2 ]. It is one of the most common consequences of injuries in the elderly population [ 3 ]. Despite advances in surgical techniques and medical care, the risk of nonunion and avascular necrosis (AVN) of femoral head after fixation have not changed appreciably in the last 50 years [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of hip fracture mortality in Eastern Europe are scarce [ 10 , 11 ]. However, the data in this region suggests a sex-specific difference in the incidence of hip fractures between Eastern and Western Europe [ 12 14 ], and the age and sex-specific all-cause mortality rates in Eastern Europe differ from those in Western countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies, including a systematic review, have reported lower mortality rates at 1 year than the Estonian rate at 6 months (Kurtinaitis et al. 2012, Diamantopoulos et al. 2013, Brozek et al.…”
Section: Discussionmentioning
confidence: 99%